Hoes or Adzes? Experimental Reproduction and Uses of Deer Antler Tools from the Bronze Age Terramara of Pragatto (Italy) - Arianna Durante; Sara Maria Stellacci; Alessio Pellegrini; Antonella de Angelis; Federico Scacchetti (EXARC Journal)
This research aimed to evaluate the hypotheses related to the production and possible uses of a class of deer antler tools from the Bronze Age Terramara of Pragatto (Italy). These bevel-ended instruments are traditionally considered handled hoes, related to agricultural purposes such as tillage. The aim of this work was to provide an alternative interpretation of their function, possibly linked to the different morphology of their active areas. A first experimental protocol was developed to create a reference collection of the archaeological antler tools to provide information on the manufacturing technology adopted by the ancient craftsmen approximately 3500 years ago. The second stage of the experiment allowed us to assess the potential versatility of the replicated artefacts from a functional point of view, as some of them have also shown great effectiveness in woodworking activities. The final comparison between traces through a microscopic analysis of the surfaces was essential to support this latter functional hypothesis. This study allowed us to determine which tools and methods were required to produce these artefacts and, ultimately, to identify their possible multifunctions, offering perspectives in understanding their economic role within the Pragatto population.